2006
DOI: 10.1001/archneur.63.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Wilson Disease With Ammonium Tetrathiomolybdate

Abstract: Objective: To compare tetrathiomolybdate and trientine in treating patients with the neurologic presentation of Wilson disease for the frequency of neurologic worsening, adverse effects, and degree of neurologic recovery. Design: A randomized, double-blind, controlled, 2-arm study of 48 patients with the neurologic presentation of Wilson disease. Patients either received 500 mg of trientine hydrochloride 2 times per day or 20 mg of tetrathiomolybdate 3 times per day with meals and 20 mg 3 times per day between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(85 citation statements)
references
References 16 publications
0
83
0
2
Order By: Relevance
“…It was found that tetrathiomolybdate was superior to trientine. In this study, 6 out of 23 (26%) patients on trientine deteriorated [23,24]. The patients who deteriorated on penicillamine are a great challenge and the safety and efficacy of alternative drugs including trientine needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that tetrathiomolybdate was superior to trientine. In this study, 6 out of 23 (26%) patients on trientine deteriorated [23,24]. The patients who deteriorated on penicillamine are a great challenge and the safety and efficacy of alternative drugs including trientine needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Value in mean ± SD or median (range) (Brewer et al 1987). In another randomized controlled trial, 6 out of 23 patients on trientine had deterioration and 3 of them died, whereas only 1 out of 25 deteriorated on tetrathiomolybdate (Brewer et al 2006). Asymptomatic WD patients are less likely to have worsening compared to symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of neurologic deterioration following chelating therapy is not known, but studies have suggested redistribution of Cu from the hepatic and visceral organs to the brain (Bruha et al 2012;Chen et al 2012;Choi and Zheng 2009;Halliwell 2001;Stuerenburg 2000;Gromadzka et al 2014;Brewer et al 2003Brewer et al , 2006Brewer et al , 2009. Moreover, there may be shifting of Cu from various intra-neuronal locale following chelating treatment (Chen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 14 studies were identified [2,3,5,9,11,13,15,[18][19][20][21][23][24][25]. These are summarised in Table 4.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…None of the studies had a sample size calculation. Only one study was a randomised controlled trial [5], but the outcome was not clearly defined and many participants had previous exposure to other chelation, which had not been controlled for (level IC). Three studies were prospective evaluations of copper clearance comparing trientine to penicillamine (level IIIB).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%